PENGARUH TATA KELOLA PERUSAHAAN TERHADAP TAX AVOIDANCE DI BURSA EFEK INDONESIA (Studi Kasus Pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Khoiru Ummah Adiningsih; Triyono Triyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research aims to determine the effect of corporate governance on tax avoidance as measured by the expertise or financial background of the audit committee, independent commissioners, executive compensation, public share ownership structure, largest share ownership structure, company size, and company performance. The sample in this research is a manufacturing company in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2017 to 2020. The sampling technique used the purposive sampling method by applying certain criteria to obtain 152 samples consisting of 38 companies. The method used in this research is quantitative method with classical assumption test and multiple linear regression test. The result showed that the company’s performance had an effect on tax avoidance. Meanwhile, the audit committee’s expertise or financial background variables, independent commissioners, executive compensation, public share ownership structure, largest share ownership structure, and company size did not have an effect on the tax avoidance variable.